Antropologi Gerakan Sosial: Membaca Transformasi Identitas Budaya di Kota Manokwari, Papua Barat - I Ngurah Suryawan (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2011)
This article elaborate anthropology of social movement engage transformation of cultural identity. Increasing complexity of the transformation of cultural identity in Papua which resulted from a series of regional expansion, local power struggle for control of the resources of political economy. In this article, anthropology of social movement used reflective method by creating collectively with his subject of study a pattern of relation in order to formulate the problem and give his argumentation. This method of study is categorized as participatory alternative (transformative) study believing that the fact is participative in nature and is created by the (relation) of the mind and the existing environment. It is known as “critical subjectivity” occurring through our participatory transaction with our environment. The ethnographic method in this study contains reflective process rather than objective value-free findings. In the words of Laksono (2009a), the study goes forward with the community whom he investigates in a (new) history-making sociocultural process. Thus, this method of study makes anthropological study as part of the social movement in its community that required participation in creating an inseparable history from the community in which the study is conducted. In reference to the study of Tsing (2005 through Laksono, 2009b), the local people in the Land of Papua is argued live at the frontier, encountering global powers’ exploitation both in natural and human resources. In this context, the strategies applied by the Papuan people in building their cultural identity will be used to inspire other local communities in Indonesia and around the world not being foolish and easily crushed by globalization processes.